439 DEVELOPMENT OF AN INTEGRATED PATIENT-SPECIFIC QUALITY ASSURANCE PROGRAM IN RADIATION THERAPY: A PILOT PROJECT BY THE GASTROINTESTINAL SITE GROUP. (1st January 2006) - Barrett, K.; Medlam, G.; Ditomasso, A.; Price, J.; Kelly, V.; Wong, R.; Warde, P.; Brierley, J.; Bissonnette, J-P
Abstract : Purpose: To design and evaluate a QA program that would allow 100% of cases to be audited. To evaluate the feasibility and clinical value of a set of metrics and identify areas for ongoing improvement. Methods: Structured and qualitative needs assessments were conducted to elicit input from all stakeholders within the gastrointestinal (GI) site group (radiation oncologists, therapists, planners, physicists) to identify relevant metrics. Criteria for scoring these metrics were compiled. During the pilot period, the frequency of QA rounds were adjusted from twice monthly to weekly to facilitate the audit of cases to occur within 1 week of the radiation start date. All peer review sessions were multidisciplinary with a minimum requirement of 2 GI radiation oncologist. Results: Between August 30, 2004 and July 18, 2005, 258/337 (77%) GI cases identified prospectively were audited. Of these, 194 (75%) cases were approved as planned, 49 (19%) cases were approved after discussion, and in 15 (6%) cases revision was recommended. In 54 (21%) cases, no treatment protocols were applicable, typically because the cases were palliative. The process identified areas for improvement (eg, the need for new techniques for certain types of esophageal and stomach cases) and gaps within existing protocols requiring modification and reinforced the implementation of site group policies. Conclusion: The model was effective in increasing the proportion of cases that were submitted for peer review and in identifying issues for ongoing improvement. The process of developing the current model promoted motivation and compliance.